PENGARUH BELANJA MODAL DAN TENAGA KERJA TERHADAP PERTUMBHAN EKONOMI (Studi Pada Kota Medan Tahun 2012-2016) - Evalina Pakpahan (JURNAL MANAJEMEN DAN BISNIS, 2018)
This research aims to test the effect of capital expenditure and labor to economic growth on Medan City from 2012 – 2016. This study used time series and the analysis technique used multiple linier regression analysis model with ordinary least square method (OLS). The results show that capital expenditure and labor have positive effect but it is not significant to economic growth on Medan City.